Reducing risks to life : measurement of the benefits - Bailey, Martin J. (Washington : American Enterprise Institute for Public Policy Research, 1980)
The book has three chapters covering: Managing Resources to Maximize Lives Saved; The Logic of Benefit-Cost Analysis; How Much is Enough? and conclusion.
Includes bibliographical footnotes.
rpm 19/02/2018
Loans
Keywords: Industrial safety; Industrial policy; Environmental policy